Policy analysis in the field of rare diseases in China: a combined study of content analysis and Bibliometrics analysis - Li, Xiaotao; Wu, Lan; Yu, Lina; He, Youqin; Wang, Min; Mu, Yan (Frontiers in Medicine, 2023)
Introduction The Chinese government has made significant strides in addressing the needs of individuals affected by rare diseases in recent years. This paper aims to provide a comprehensive analysis of national rare disease policies in China from 2009 to 2022, using a mixed-methods approach. Methods A two-dimensional analytical framework, which includes policy tools and policy themes, is introduced to analyze the rare disease policies comprehensively. Drawing on the policy tools theory proposed by Rothwell and Zegveld, this paper evaluates the tools used in rare disease policies. Co-word analyses and network analyses are employed to identify key themes in rare disease policies and collaboration among government departments. Results The rare disease policy landscape in China is undergoing rapid growth, with an increasing number of government departments involved in policy formulation. However, further collaboration between departments is needed to strengthen these policies. Environment-based and supply-based tools are preferred in rare disease policies. The policy themes can be grouped into four categories: (1) Registration, Approval and Supply of Rare Disease Drugs, (2) Construction of Diagnosis and Treatment System for Rare Diseases, (3) Development and Genericization of Rare Disease Drugs, and (4) Social Security for Patients with Rare Diseases. Discussion The study provides valuable insights into the current state of rare disease policies in China and offers suggestions for policy improvement. The results show that the Chinese government has made efforts to address the needs of individuals affected by rare diseases, but there is still room for improvement. The collaboration between government departments needs to be strengthened to achieve better rare disease policies. The findings of this study have implications for other countries with similar healthcare systems and can contribute to a better understanding of the impact of rare disease policies on public health.